2017
DOI: 10.5433/1679-0359.2017v38n4supl1p2351
|View full text |Cite
|
Sign up to set email alerts
|

Productive characteristics of banana genotypes submitted to different irrigation water depths under Cerrado conditions

Abstract: Irrigation management associated with other banana agricultural practices can provide an increased productivity and improved fruit quality. This study assessed the productive characteristics of banana genotypes under different irrigation water depths. The experiment was conducted at the experimental area of the School of Agronomy (EA/UFG) in Goiânia, GO, Brazil. The experimental design was a split-plot randomized block design, in which four irrigation water depths (30, 65, 100, and 135% of crop potential evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The genotypes PA94-01, FHIA 02, Maravilha, Thap Maeo and FHIA 23 presented higher productivity in the first cycle, and PA94-01, FHIA 02, Maravilha, Thap Maeo, and FHIA 18 in the second and third cycles (Table 6). In the last two cycles, the genotype FHIA 18 presented productivity above 24 t ha -1 , a value close to that found by Ootani et al (2017), but smaller than the value determined by Silva et al (2017). The genetic materials with higher bunch weight were also the most productive.…”
Section: Number Of Handssupporting
confidence: 74%
See 1 more Smart Citation
“…The genotypes PA94-01, FHIA 02, Maravilha, Thap Maeo and FHIA 23 presented higher productivity in the first cycle, and PA94-01, FHIA 02, Maravilha, Thap Maeo, and FHIA 18 in the second and third cycles (Table 6). In the last two cycles, the genotype FHIA 18 presented productivity above 24 t ha -1 , a value close to that found by Ootani et al (2017), but smaller than the value determined by Silva et al (2017). The genetic materials with higher bunch weight were also the most productive.…”
Section: Number Of Handssupporting
confidence: 74%
“…In the first production cycle, highlighted by the largest number, Thap Maeo, PA94-0, FHIA 23, YB42-17, FHIA 02 and Caipira; in the second cycle, Thap Maeo, and in the third cycle, Thap Maeo. It was observed an increase in the total number of fruits in the first two cycles (without statistical differences between them) for the third cycle in the genotypes YB42-17 and Caipira, as well as from the first to second and third cycles (without statistical differences between the last two) regarding the YB42-47, Maravilha,Thap Maeo, Despite the differences detected between genotypes and cycles, comparing the results of this study with other, between the same cultivars, one can notice that the total number of fruits are inferior in this study (Nomura et al, 2013b;Silva et al, 2013b;Ribeiro et al 2013;Rodrigues Filho et al, 2014;Roque et al, 2014;Silva et al, 2016;Silva et al, 2017). Thus, two hypotheses could explain this discrepancy, 1 st ) cultivars are not adapted to the conditions of Rio Branco or; 2 nd ) the management dispensed to the orchard was not enough for the genotypes to express a greater quantity of fruit.…”
Section: Number Of Handsmentioning
confidence: 42%
“…They found that the ET of banana increased from March, peaked in June and July and decreased again. Silva et al (2017) also found almost the same trend, as the ET of banana was the lowest from October to March and increased from April to September.…”
Section: Resultsmentioning
confidence: 58%
“…Irrigated agriculture aims to maximize production while maintaining quality standards at the lowest possible cost without degrading the environment. The development of better irrigation procedures is necessary to overcome water restrictions resulting from the increased demand and the limited resources available (SILVA et al, 2017). In this context, soil moisture has been recognized as an important factor to understand the hydrological and meteorological processes, separating evapotranspiration from precipitation, runoff, and infiltration (TRAN et al, 2015;SANTOS et al, 2016), with the need to develop techniques for continuous soil moisture measurements (KAPILARATNE; LU, 2017).…”
Section: Introductionmentioning
confidence: 99%